Presymptomatic cerebral blood flow changes in CHMP2B mutation carriers of familial frontotemporal dementia (FTD-3), measured with MRI. Issue 2 (15th March 2012) - Lunau, Line; Mouridsen, Kim; Rodell, Anders; Østergaard, Leif; Nielsen, Jørgen Erik; Isaacs, Adrian; Johannsen, Peter; ,
Abstract : Objectives: To assess functional changes measured by cerebral blood flow (CBF) in the presymptomatic stage of frontotemporal dementia linked to chromosome 3 (FTD-3) caused by a truncating mutation in CHMP2B . Design: Case–control study. Setting: A memory clinic and tertiary referrals centre for dementia and inherited neurodegenerative disorders. Participants: The authors included 11 presymptomatic CHMP2B mutation carriers and seven first-degree-related family non-carriers. Participants were MRI scanned twice with an interval of 15 months. Primary and secondary outcome measures: Local functional changes in brain tissue perfusion were measured as CBF with two different MR techniques, gradient echo (GRE) and spin echo (SE), focusing on CBF in all cerebral vessels (GRE) and cerebral capillaries (SE), respectively. As planned, data analysis included co-registration of perfusion images to structural T1 images. Perfusion data were then extracted from seven regions-of-interest, normalised to white matter and statistically compared between carriers and non-carriers. Results: For SE, contrasts between carriers and non-carriers showed significant differences in temporal, occipital and parietal lobes and in hippocampus. There was no evidence of changes from baseline to follow-up. For GRE, there were no significant differences between carriers and non-carriers. Conclusions: Significantly decreased CBF was found in presymptomatic CHMP2B mutation carriers in occipital-and parietal lobes. Comparing SE with GRE, data indicate that FTD-3 vascular pathology might primarily affect brain capillaries.